A Text Analysis of Four Levels of Librarian Involvement and Impact on Students in an Inquiry-Based Learning Course - Stoeckle, Marc; Lenart, Bartlomiej; Murphy, James E. (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2022)
Librarians at the University of Calgary collaborated with instructors on an inquiry-based learning course with varying involvement across four course sections. This study uses text analysis of student assignments to assess information literacy (IL) skill development across four levels of course participation: librarian as instructor-of-record, two levels of embeddedness, and a single ‘one-shot’ session. The methodology included the tracking of keywords generated using the ACRL Framework for Information Literacy and text analysis of student reflection assignments in an inquiry-based, research-focused first-year undergraduate course. The results suggest that the benefit to student IL skills is not related to amount of librarian instruction, but rather to the level of instructor buy-in with regard to library services and the importance of IL skills. We argue that the most impactful librarian involvement is as an IL course consultant rather than a full-time embedded librarian (which is surprising given the literature on the efficacy of embeddedness). Although further research is needed, the study results have significant implications for academic librarian instructional practices and collaborations on course content with faculty members.